Live migration of trans-cloud applications. - Carrasco Mora, José Manuel; Durán-Muñoz, Francisco Javier; Pimentel-Sánchez, Ernesto (Elsevier, 2020)
The development of applications independent of the cloud providers where they are going to be deployed is still an open issue. In fact, cloud agnostic software development presents important challenges to be solved. One of these issues is the runtime migration of components. Even more difficult is dealing with the interoperability issues when the migration also implies a change of provider or service level. This paper presents a solution for the component-wise migration of cloud applications. The migration is performed component-wise in the sense that each component of the application to be migrated, which may be deployed on a specific service on a specific provider, may individually be moved to a different one. Our solution relies on the three key ingredients of the transcloud approach, where the CAMP and TOSCA standards play a central role: a CAMP-based unified API, TOSCA-based agnostic topology descriptions, and mechanisms for the independent specification of target service locations. The effort and the time required for restoring the activity of applications are used as metrics to evaluate the performance of the proposed migration orchestrator. Although the time required for the migration operation is directly related to the topology of the application, the affected components, and their previous and target locations, the downtimes are significantly reduced. Moreover, thanks to the abstraction level at which it operates and the automation provided, the effort needed from the user for a migration operation is almost zero. We present an implementation of our proposed solution and illustrate it with a case study and experimental results.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/27884
Keywords: Informática en la nube; Aplicaciones informáticas; Cloud; TOSCA; CAMP; Apache Brooklyn; Application migration; Heterogeneous deployment